3D‐printed chip for detection of methicillin‐resistant Staphylococcus aureus labeled with gold nanoparticles. Issue 3 (3rd October 2014) - Chudobova, Dagmar; Cihalova, Kristyna; Skalickova, Sylvie; Zitka, Jan; Rodrigo, Miguel Angel Merlos; Milosavljevic, Vedran; Hynek, David; Kopel, Pavel; Vesely, Radek; Adam, Vojtech; Kizek, Rene; Foret, Franta; et al.
<x xml:space="preserve">Abstract</x> Methicillin‐resistant Staphylococcus aureus (MRSA) is a dangerous pathogen occurring not only in hospitals but also in foodstuff. Currently, discussions on the issue of the increasing resistance, and timely and rapid diagnostic of resistance strains have become more frequent and sought. Therefore, the aim of this study was to design an effective platform for DNA isolation from different species of microorganisms as well as the amplification of mecA gene that encodes the resistance to β‐lactam antibiotic formation and is contained in MRSA. For this purpose, we fabricated 3D‐printed chip that was suitable for bacterial cultivation, DNA isolation, PCR, and detection of amplified gene using gold nanoparticle (AuNP) probes as an indicator of MRSA. Confirmation of the MRSA presence in the samples was based on a specific interaction between mecA gene with the AuNP probes and a colorimetric detection, which utilized the noncross‐linking aggregation phenomenon of DNA‐functionalized AuNPs. To test the whole system, we analyzed several real refractive indexes, in which two of them were positively scanned to find the presence of mecA gene. The aggregation of AuNP probes were reflected by 75% decrease of absorbance (λ = 530 nm) and change in AuNPs size from 3 ± 0.05 to 4 ± 0.05 nm (n = 5). We provide the one‐step identification of mecA gene using the unique platform that employs the rapid, low‐cost, and easy‐to‐use colorimetric method for MRSA detection in various samples.